The Effect of Optimizing Digital and Information Literacy in Writing Scientific Articles on Students' Critical Thinking Skills - Imas Cintamulya; Lilik Mawartiningsih; Warli Warli (STAI Hubbulwathan Duri, 2023)
Writing scientific articles that are integrated with learning biology is still rarely done. On the other hand, students' critical thinking skills need to be developed. One of the efforts is to develop students' thinking skills by writing scientific articles by optimizing digital and information literacy use. Scientific articles are used as student assignments in learning conservation and environmental knowledge through the group investigation learning model. This study aims to determine the effect of writing scientific articles through optimizing digital and information literacy on students' critical thinking skills. The method used in this research is quantitative with a non-experimental explanatory design. Data collection using a questionnaire with a Five Point Likert Scale. There were 43 respondents, of which 100 percent of the completed questionnaire was usable for further analysis. Data analysis in this study used a structural equation model with a partial less square analysis technique (SEM-PLS) using smart-pls 3.2.7 software at a significance level of 5% to predict the hypothesis. Structural Equation Modeling Estimation Shows that Digital Literacy, Information Literacy, and Article Writing Affect Students' Critical Thinking Skills. These findings indicate that writing scientific articles through optimizing digital and information literacy has an effect on students' critical thinking skills. Therefore, writing scientific articles through optimizing digital and information literacy is one method to improve students' critical thinking skills. The implication in the world of education, writing scientific articles through optimizing digital and information literacy can be used as an alternative task for students to improve critical thinking skills.